Patterns of Stepfamily Relationship Quality and Adolescents’ Short-Term and Long-Term Adjustment - Jensen, Todd M. (J Fam Psychol, 2018)
Stepfamilies experience unique dynamics with implications for family functioning and youth well-being. Emerging research is incorporating a holistic perspective, whereby stepfamily dynamics are viewed more comprehensively, and constellations of stepfamily relationship quality are identified. The current study examines short-term and long-term associations between latent patterns of stepfamily relationships (including the quality of mother-child, stepfather-child, nonresident father-child, and stepcouple dyads) and youth adjustment (i.e., depression, delinquency, self-esteem) across three stages of youth development: adolescence, emerging adulthood, and young adulthood. Using a representative sample of adolescents from the National Longitudinal Study of Adolescent to Adult Health, results from longitudinal structural equation models and latent growth curve models indicate that youth adjustment over time is optimized among youth in a residence-centered (i.e., high-quality relationships among mother-child, stepfather-child, and stepcouple dyads) or inclusive (i.e., high-quality relationships across all dyads, including the nonresident father) pattern, as compared to youth in an unhappy couple (i.e., low-quality stepcouple relationship) or parent-child disconnection (i.e., low-quality relationships between youth and each parental figure) pattern. The results point to many similarities between male and female youth in terms of adjustment responses to patterns of stepfamily relationships, although some differences are apparent. In the context of stepfamily relationships marked by low-quality relationships, male youth might exhibit greater initial levels of externalizing problems compared to female youth; whereas female youth might exhibit greater initial levels of internalizing problems compared to male youth. Implications for future research and intervention and prevention efforts are discussed.